Traditional Serrated Pathway–associated Colorectal Carcinoma: Morphologic Reappraisal of Serrated Morphology, Tumor Budding, and Identification of Frequent PTEN Alterations. (August 2019) - Tsai, Jia-Huei; Jeng, Yung-Ming; Yuan, Chang-Tsu; Lin, Yu-Lin; Cheng, Mei-Ling; Liau, Jau-Yu
Abstract : The phenotypic characteristics of traditional serrated adenoma (TSA)-associated malignancies remain obscure. This study was a morphologic reappraisal of 27 colorectal carcinomas arising from TSA (TSA-CRCs) and 53 BRAF -mutated/microsatellite-stable colorectal carcinomas ( BRAF -mut/MSS CRCs). Makinen's criteria for serrated adenocarcinoma were applied to assess the morphologic similarity of the 2 entities. Tumor budding, another histologic feature of serrated adenocarcinoma, was also evaluated. Phosphatase and tensin homologue deleted on chromosome 10 ( PTEN ), a commonly mutated gene in the serrated pathway, was assessed with immunohistochemistry. Tumors with aberrant PTEN expression were subjected to molecular analysis using quantitative methylation assay, exon sequencing, and fluorescence in situ hybridization. Most cases (>90%) of TSA-CRCs and BRAF -mut/MSS CRCs exhibited a constellation of serrated morphology, including epithelial serrations, abundant eosinophilic cytoplasm, and discernible/vesicular nuclei. A majority (65%) of them qualified for the diagnosis of serrated adenocarcinoma. High-grade tumor budding was closely associated with serrated morphology and was a significant independent factor for poor patient survival in multivariate analysis ( P =0.008). Aberrant PTEN expression was detected in nearly half of the cases of both entities ( P =0.501). Among the 44 samples with aberrant PTEN expression, 8 harbored PTEN somatic mutations, which were characterized by random distribution without hotspot clustering, 12 had promoter hypermethylation, and 14 had deleted alleles. These findings support a unique model of colorectal carcinogenesis that is similar between TSA-CRCs and BRAF -mut/MSS CRCs. Both entities exhibited common histologic patterns and similar molecular alterations and may well constitute the TSA pathway. Abstract : Supplemental Digital Content is available in the text.